On Being in Nature: Aldo Leopold as an Educator for the 21st Century - Jónsson, Ólafur; Thorsteinsson, Jakob; Árnadóttir, Hervör; Gísladóttir, Karen (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2020)
The paper describes activities and reflections during and after a four day outdoor education course from the point of view of four educators: a philosopher, an outdoor educator, social work educator and a literacy educator. During the course, various philosophical and educational activities and ideas were put to the test, issues such as slowness, solitude, and silence were both practiced, discussed, and reflected on. After the course, reflecting on the whole experience, ideas from Aldo Leopold on conservation aesthetics are used to make a case for a certain kind of environmental education, and David Orr’s account of myths of education are used to argue for the importance of such education. To develop the ideas further, the paper discusses both recent neoliberal trends that are affecting educational systems around the globe, and also issues such as the difference between situated knowledge and representational knowledge, and the significance of language and perception for human connection with nature.